(untitled) (Journal of Fiber Bioengineering and Informatics, 2009)
The poor crease recovery performance of linen fabrics has resulted in attempts to improve this characteristic by modifying the structure of the flax fibres from which the linen is woven. In this paper, flax fibers were oxidized with sodium periodate solution leading to a variety of polymers having functional groups such as aldehyde group for subsequent modification. Several factors (oxidant concentration, pH values, oxidization temperature and time) on the weight loss, mechanical properties and content of the formed aldehyde groups were analyzed. Structure and morphology of oxidized flax fibers were also investigated. Results show that the characteristic absorption band due to aldehyde group strengthened the oxidized fibers. The crystallinity decreased and endothermic decomposition temperature dropped gradually with the increase of oxidant concentration, oxidation time and temperature, as well as their mechanical properties. Moreover, when the fiber was oxidized with high level oxidization degree, the conformation of flax completely transferred to a random coil. So as a textile material, the oxidization degree of flax should be reasonably controlled.